2013
DOI: 10.1128/aac.02468-12
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid, Rifampin, and Pyrazinamide Plasma Concentrations in Relation to Treatment Response in Indonesian Pulmonary Tuberculosis Patients

Abstract: f Numerous studies have reported low concentrations of antituberculosis drugs in tuberculosis (TB) patients, but few studies have examined whether low drug concentrations affect TB treatment response. We examined steady-state plasma concentrations of isoniazid, rifampin, and pyrazinamide at 2 h after the administration of drugs (C 2 h ) among 181 patients with pulmonary tuberculosis in Indonesia and related these to bacteriological response during treatment. C 2 h values below reference values for either isoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
76
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 31 publications
14
76
3
4
Order By: Relevance
“…In the study by Zhu et al, the average C max and AUC values were 38 g/ml and 373 g · h/ml, respectively, whereas they were 30.8 g/ml and 307 g · h/ml, respectively, in our study, despite the use of similar doses on a milligram-per-kilogram basis (15). Previous clinical studies have shown that a C max of Ͻ35 g/ml or an AUC of Ͻ363 mg · h/ml is associated with treatment failure (10,12,18). However, it is important to note that antimicrobial activity is not linked to the drug concentration alone but is linked to a combination of the drug concentration and the susceptibility of the infecting strain to the antibiotic of interest (the MIC).…”
Section: Discussioncontrasting
confidence: 47%
“…In the study by Zhu et al, the average C max and AUC values were 38 g/ml and 373 g · h/ml, respectively, whereas they were 30.8 g/ml and 307 g · h/ml, respectively, in our study, despite the use of similar doses on a milligram-per-kilogram basis (15). Previous clinical studies have shown that a C max of Ͻ35 g/ml or an AUC of Ͻ363 mg · h/ml is associated with treatment failure (10,12,18). However, it is important to note that antimicrobial activity is not linked to the drug concentration alone but is linked to a combination of the drug concentration and the susceptibility of the infecting strain to the antibiotic of interest (the MIC).…”
Section: Discussioncontrasting
confidence: 47%
“…Low systemic exposure levels to RIF have been recently shown to have a direct correlation with mortality rates in TBM patients with high exposure levels (600mg IV) being associated with significantly lower mortality than low exposure levels (450mg orally) 21 . A recent study has investigated, in children with TBM, the CSF exposure to anti-tubercular drugs and found that at a dose of 10mg/kg, rifampicin levels are lower than the minimum inhibitory concentration of susceptible bacteria 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The data generated suggest that a a 900mg oral dose would be more appropriate in this patient cohort based on the assumptions of the model (Figure 4, B). Increasing RIF dose in fact significantly improves survival rates among TBM patients according to the latest clinical studies where it has been shown that a high dose of 600mg RIF administered intravenously to TBM patients significantly improved the clinical outcome for these patients 21 . Additionally, according to literature data 31 , the systemic exposure that would be anticipated to be achieved in the current cohort with a higher 900mg dose is predictive of CSF exposures that exceed the required TB MIC value of RIF in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…This review failed to draw a firm association between serum drug concentrations and treatment outcome. A study from Indonesia showed that though low RMP, INH, and PZA concentrations occurred in many patients even with the DOT strategy, most patients had a good treatment outcome (30). Narita and colleagues did not find an association between TB recurrence and the serum levels of anti-TB drugs (31).…”
Section: Discussionmentioning
confidence: 99%